2022
DOI: 10.1186/s12960-022-00726-z
|View full text |Cite
|
Sign up to set email alerts
|

Medical education interventions influencing physician distribution into underserved communities: a scoping review

Abstract: Background and objective Physician maldistribution is a global problem that hinders patients’ abilities to access healthcare services. Medical education presents an opportunity to influence physicians towards meeting the healthcare needs of underserved communities when establishing their practice. Understanding the impact of educational interventions designed to offset physician maldistribution is crucial to informing health human resource strategies aimed at ensuring that the disposition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 134 publications
2
17
0
1
Order By: Relevance
“…13 Physician maldistribution is a global problem that hinders patients' ability to access healthcare services. 28 Physicians are geographically maldistributed, with too few physicians in rural areas. 29,30 In Japan, there is a well-documented issue of physician shortages and regional maldistribution, where approximately 90% of physicians are clustered in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…13 Physician maldistribution is a global problem that hinders patients' ability to access healthcare services. 28 Physicians are geographically maldistributed, with too few physicians in rural areas. 29,30 In Japan, there is a well-documented issue of physician shortages and regional maldistribution, where approximately 90% of physicians are clustered in urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Bolstering the rural obstetrician–gynecologist workforce is important to mitigate maternal morbidity and mortality in the United States. Elma et al ( 6 ) reported that physician shortage and maldistribution hinder patients' ability to access healthcare services in rural areas, which in turn contributes to a higher incidence of chronic diseases, injury, and mortality. Studies in China have shown that population health is affected by health resource distribution ( 7 – 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several medical education policies have been reported to positively influence FP practice locations, 15 including selecting medical students from underserved areas 16–19 and/or providing medical training in underserved areas 13,16,17,20–22 . These approaches are usually justified with explanations consistent with Social Attachment Theory, which describes the influence of secure relationships on one's decision making 23 .…”
Section: Introductionmentioning
confidence: 99%